Solitary fibrous tumor of the orbit presenting in pregnancy - Das, Jayanta K (Medknow Publications, 2009)
A 32-year-old woman, three months pregnant, reported with the complaint of protrusion of the right eye for six months. She gave history of rapid protrusion of eyeball for the last two months along with the history of double vision for the last one month. Computer tomography (CT) scan revealed a well-defined mass lesion in the intraconal space of the right orbit which was excised through a lateral orbitotomy approach. Histological examination and immunohistochemistry revealed a solitary fibrous tumor, which showed a rapid progression in pregnancy.